Emergency overcrowding and access block: A smaller problem than we think. Issue 2 (8th November 2018) - Innes, Grant D.; Sivilotti, Marco L.A.; Ovens, Howard; McLelland, Kirstie; Dukelow, Adam; Kwok, Edmund; Chopra, Anil; Cheng, Ivy; Kalla, Dan; Mackinnon, David; Kim Sing, Chad; Barclay, Neil; et al.
ABSTRACT: Objectives: Emergency department (ED) access block, the inability to provide timely care for high acuity patients, is the leading safety concern in First World EDs. The main cause of ED access block is hospital access block with prolonged boarding of inpatients in emergency stretchers. Cumulative emergency access gap, the product of the number of arriving high acuity patients and their average delay to reach a care space, is a novel access measure that provides a facility-level estimate of total emergency care delays. Many health leaders believe these delays are too large to be solved without substantial increases in hospital capacity. Our objective was to quantify cumulative emergency access blocks (the problem) as a fraction of inpatient capacity (the potential solution) at a large sample of Canadian hospitals. Methods: In this cross-sectional study, we collated 2015 administrative data from 25 Canadian hospitals summarizing patient inflow and delays to ED care space. Cumulative access gap for high acuity patients was calculated by multiplying the number of Canadian Triage Acuity Scale (CTAS) 1-3 patients by their average delay to reach a care space. We compared cumulative ED access gap to available inpatient bed hours to estimate fractional access gap. Results: Study sites included 16 tertiary and 9 community EDs in 12 cities, representing 1.79 million patient visits. Median ED census (interquartile range) was 66, 300 visits per year (58, 700-80, 600). High acuity patients accounted for 70.7% of visits (60.9%-79.0%). The mean (SD) cumulative ED access gap was 46, 000 stretcher hours per site per year (± 19, 900), which was 1.14% (± 0.45%) of inpatient capacity. Conclusion: ED access gaps are large and jeopardize care for high acuity patients, but they are small relative to hospital operating capacity. If access block were viewed as a "whole hospital" problem, capacity or efficiency improvements in the range of 1% to 3% could profoundly mitigate emergency care delays. Résumé: Contexte: Le blocage de l'accès aux services des urgences (SU), soit l'impossibilité de fournir des soins appropriés en temps opportun aux patients en état grave, est la préoccupation première des SU quant à la sûreté des patients, dans les pays industrialisés. La principale cause du blocage de l'accès au SU est le blocage de l'accès à l'hôpital, qui conduit au séjour prolongé des malades hospitalisés, sur civière, au SU. L'écart cumulé d'accès au SU, soit le produit du nombre de patients en état grave à l'arrivée par le délai d'attente moyen avant l'arrivée dans une salle d'examen, constitue une nouvelle mesure d'accès qui fournit une approximation des délais d'attente totaux, au niveau des établissements, avant la prestation de soins d'urgence. Bon nombre de dirigeants sont d'avis que les délais d'attente sont trop importants pour être résolus sans une augmentation importante de la capacité d'hospitalisation des malades. L'étude visait donc à quantifier les blocages cumulés de l'accès au SU (le problème) sous forme de fraction de la capacité d'hospitalisation des malades (la solution possible), dans un large échantillon d'hôpitaux au Canada. Méthode: Il s'agit d'une étude transversale, dans laquelle ont été recueillies des données administratives de 2015, provenant de 25 hôpitaux et fournissant un résumé de l'afflux des patients et des délais d'attente avant l'arrivée dans une salle d'examen au SU. L'écart cumulé d'accès chez les patients en état grave a été calculé en multipliant le nombre de patients dont l'état était de niveau I à III selon l'Échelle canadienne de triage et de gravité par les délais d'attente moyens avant l'arrivée dans une salle d'examen. Il y a eu, par la suite, comparaison entre l'écart cumulé d'accès au SU et le nombre d'heures-lits disponibles pour les malades hospitalisés, afin d'estimer la fraction de l'écart d'accès. Résultats: L'étude comptait 16 SU tertiaires et 9 SU communautaires, répartis dans 12 villes, qui totalisaient 1, 79 million de consultations. La valeur médiane (écart interquartile) du dénombrement des visites au SU s'élevait à 66 300 consultations par année [58 700 – 80 600]. Les patients en état grave pesaient pour 70, 7 % des consultations [60, 9 % – 79, 0 %]. L'écart cumulé moyen (écart type) d'accès au SU était de 46 000 heures-civières, par SU, par année (± 19 900), soit 1, 14 % (± 0, 45 %) de la capacité d'hospitalisation des malades. Conclusion: Les écarts d'accès au SU sont importants et ils mettent en péril la prestation de soins aux patients en état grave, mais ils sont minimes comparativement à la capacité de fonctionnement des hôpitaux. Si les blocages d'accès étaient considérés comme un problème « global » touchant l'ensemble de l'établissement, des améliorations apportées à la capacité ou à l'efficacité, de l'ordre de 1 à 3 %, pourraient atténuer considérablement les délais d'attente avant la prestation de soins d'urgence.